Hormonal and Storage Metabolic Regulation of Germination in Toona sinensis - Linyue Liu; Zhiyuan Wang; Yu Wu; Yongbao Shen (Horticulturae)
Toona sinensis (A. Juss.) Roem, classified under the Toona genus of the Meliaceae family, is a fast-growing, woody species endemic to China, valued as both a vegetable crop and medicinal plant. Its seeds achieve rapid germination through a cascade of interconnected physiological, metabolic, and hormonal adaptations. Initially, physiological hydration is driven and accelerated by only two distinct phases of water imbibition. This hydration surge triggers storage reserve mobilization, with soluble sugars, proteins, and lipids undergoing rapid degradation during imbibition, while starch catabolism proceeds gradually—a pattern mirrored by progressive increases in enzymatic activities (amylase, protease, and acid phosphodiesterase (ACP)) that correlate with reserve reallocation. Concurrently, a metabolic shift from glycolysis to the pentose phosphate pathway (PPP) optimizes energy utilization, supporting germination acceleration. These biochemical changes are orchestrated by hormonal coordination: elevated gibberellin A3 (GA3), zeatin riboside (ZR), and indole-3-acetic acid (IAA) levels, coupled with rising GA3/ABA, IAA/ABA, and ZR/ABA ratios, temporally aligned with germination progression. Finally, structural evidence confirms successful germination completion, as cotyledon lipid droplet breakdown and starch granule synthesis directly correlate with embryonic elongation. Together, these mechanisms underscore T. sinensis’ adaptive strategy, integrating physiological plasticity, metabolic flexibility, and endocrine precision to ensure efficient germination.